Service configuration, unit characteristics and variation in intervention rates in a national sample of obstetric units in England: an exploratory analysis - Rowe, RE; Townend, J; Brocklehurst, P; Knight, M; Macfarlane, A; McCourt, C; Newburn, M; Redshaw, M; Sandall, J; Silverton, L; Hollowell, J (BMJ Publishing Group, 2014)
Objectives To explore whether service configuration and obstetric unit (OU) characteristics explain variation in OU intervention rates in ‘low-risk’ women.